Analysis of Structure and Techniques of Pancula Ndeme By Justinus Hokey on Classic Guitar Composition (Jurnal Seni Musik, 2023)
This study aims to describe the structure and techniques of playing Pancula Ndeme by Justinus Hokey on classical guitar composition. This study uses a qualitative approach. The data analyzed is the sheet music of Pancula Ndeme. The results of this study indicate that the structure of this composition consists of several parts, namely Introduction – A – B – C – A – B – Coda. There are four motifs in section A (m1, m2, m3, m4), two sentences (sentences a and a'), and two themes in each sentence. Section B consists of three motifs (n1, n2, n3), two phrases (phrase b and b'), and two themes in each sentence. Section C consists of 2 motifs (o1 and o2). The guitar playing techniques contained in this composition are the right-hand technique and the left-hand technique. The right-hand techniques found in this composition include; apoyando, tirando, and strumming techniques. The left-hand techniques contained in this composition include; slur, barre, and harmonic.